A study on employees job satisfaction in organisations - U, Jawahar Supraveen; U, Jawahar Surendra (Journal of Management and Science, 2021)
Job satisfaction shows that personal factors such as an individual needs and aspirations determine his/her attitude, along with group and organisational factors such as relationships with co-workers and supervisors and working conditions, work policies, and compensation. Job satisfaction reflects the extent to which people find gratification or fulfillment in their work. A satisfied employee tends to make positive contributions to absent less often, and to stay with the organisation. The effect of job satisfaction goes beyond organisational setting and structure. Satisfied employees are more likely to be satisfied responsible citizens. These people will hold a more positive attitude towards life in general and make for a society of more psychologically & physically healthy. Job satisfaction has been considered as state of pleasurable condition. Job satisfaction is often thought to be synonymous with job attitudes, but is important to recognize that those with different theoretical orientations may use the term somewhat differently. Some measure job satisfaction in terms of the gratification of strong needs in the work place. Others see it as the degree of divergence between what a person perceives is actually and what he expects to receive from the work and what that person performs. It can also be defined as the extent to which work is seen as providing those things that one considers conducive to one’s welfare. In yet another view, job satisfaction is considered a purely emotional response to job situation. Job satisfaction depends on several different factors such as satisfaction with pay, promotion opportunities, fringe benefits, job security, and relationship with co-workers and supervisor. Employees who have an internal locus of control and feel less alienated are more likely to experience job satisfaction,job involvement and organizational commitment.